Advances in PGPR research - Singh, H. B., Dr (CABI, 2017)
This book includes 25 contributions from vastly experienced, global experts in PGPR research in a comprehensive and influential manner, with the most recent facts and extended case studies. Also, the chapters address the current global issues in biopesticide research.